THE CONTINUOUS DRONE STRIKES OF THE UNITED STATES FOR COMBATING TERRORISM IN PAKISTAN UNDER PRESIDENT OBAMA ADMINISTRATION - Dyazt Ayoe Septianingsih (HI 16 UMY 003, 2016)
*3 This research aims to find out the reason why President Obama continued the use of the drone strikes for combating terrorism in Pakistan despite all of the negative results under President Bush administration. To analyze this event, decision making theory –rational actor model from Graham T. Allison is used as the main theoretical framework. The finding of this research shows there are two main reasons to explain President Obama behavior related to the continuous drone strikes in Pakistan. Firstly, it was effective to kill terrorists and disrupt their organization. Secondly, it is efficient, in term of cheaper financial cost, fewer civilian casualties, minimum risk on military personnel, and applicable in Pakistan. Keywords: Rational Actor Model, Drone Strikes, Terrorism, Global War on Terrorism.